Study of Elelctrical Installation Planning at Lecture Building of Widya Dharma University Pontianak - Amalia, Nabila Rizki (Faculty of Engineering, Universitas Tanjungpura, 2025)
As the population grows, the need for educational facilities increases. Therefore, Widya Dharma University Pontianak (UWDP) has developed a new 10-story building with a total floor area of 4,016 m ². The operation of the lecture building will inevitably involve the use of electrical energy. The primary function of electrical energy is to meet the needs of learning facilities, services, and the comfort of all building users to ensure smooth academic activities. This study employs a literature review and descriptive analytical method. During the planning process, several calculations were performed, including determining lighting requirements using DIALux Evo software, cross-sectional area of conductors, current rating of circuit breakers, and a cost estimate (RAB). Based on the calculations and analysis conducted, the number of light points required in each classroom is 16 points, with a total power of 336 Watts. The type of conductor used is NYM 2 Ã— 2.5 mm ² with a fuse rating of 4 Amperes. The total cost of the entire electrical installation work in the classrooms is IDR 45.817.000,00. From this study, it is hoped that an electrical installation plan compliant with SNI 6197 2020, PUIL 2020, and PLN standards can be developed, ensuring efficient and effective use of electrical energy in the academic building while providing comfort for building users.